SOME ASPECTS OF DEVELOPMENT AND IMPLEMENTATION OF EDUCATIONAL PROGRAMS IN A TECHNICAL UNIVERSITY - Igor O. Leushin; Irina V. Leushina (Высшее образование в России)
Actual questions of development and implementation of educational programs in accordance with federal state educational standards of higher education in a technical university are under consideration in the article, including the role of some educational subjects in forming the resulting competence-based profile of a graduate student. Organizational and methodic approaches to the procedure of evaluation of preparedness of a graduate student to his / her forthcoming professional activity are also in focus of the article as well as the forms of participation of an employer in implementation of educational program of graduate training. The article also traces the relevance of connection between «non-core » subjects with professional ones in a curriculum and professional tasks defined by the federal state educational standards. The ability of a student to complete professional tasks is considered as a priority in evaluating his/her preparedness to the forthcoming professional activity while taking practical training and at State Final Certification.